If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + -1)(2x + 1) = 0 Reorder the terms: 10(-1 + x)(2x + 1) = 0 Reorder the terms: 10(-1 + x)(1 + 2x) = 0 Multiply (-1 + x) * (1 + 2x) 10(-1(1 + 2x) + x(1 + 2x)) = 0 10((1 * -1 + 2x * -1) + x(1 + 2x)) = 0 10((-1 + -2x) + x(1 + 2x)) = 0 10(-1 + -2x + (1 * x + 2x * x)) = 0 10(-1 + -2x + (1x + 2x2)) = 0 Combine like terms: -2x + 1x = -1x 10(-1 + -1x + 2x2) = 0 (-1 * 10 + -1x * 10 + 2x2 * 10) = 0 (-10 + -10x + 20x2) = 0 Solving -10 + -10x + 20x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '10'. 10(-1 + -1x + 2x2) = 0 Factor a trinomial. 10((-1 + -2x)(1 + -1x)) = 0 Ignore the factor 10.Subproblem 1
Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-0.5, 1}
| 9x+2=4x-18 | | 9x+2=4x+18 | | 4x+13=9x-8 | | 24x+22x^2-30x^3= | | 44+44*3= | | x^3-x^2-30x= | | 6a(5a-6)=0 | | 5b^2-13b-6=0 | | 24+4y-4=0 | | 2=1+x | | -3mx=-y-2b | | 8a-12=12 | | 7y=2+3 | | 12m+9+7-1=20 | | 2b-3=16 | | a^2+b^2+c^2=d^2 | | 4x+1-5=12 | | x^2=3x+5 | | 12y-5=2 | | 4a+4=8 | | 3x^2+17x-6= | | 3x^2+17-6= | | 2X+35-15=20 | | 49-64x^2=0 | | 5n+25g=5.65 | | -7x-3y-2+7x= | | x+5y=57 | | x+5y= 57 | | -3x+4y=76 | | -6b+13b= | | 12b+3+2=20 | | n=2(l+w)-4 |